Intraocular lens power adjustment by a femtosecond laser: In vitro evaluation of power change, modulation transfer function, light transmission, and light scattering in a blue light–filtering lens. Issue 2 (February 2018) - Nguyen, Jason; Werner, Liliana; Ludlow, Jason; Aliancy, Joah; Ha, Larry; Masino, Bryan; Enright, Sean; Alley, Ray K.; Sahler, Ruth
Abstract : Purpose : To evaluate intraocular lens (IOL) power, modulation transfer function (MTF), light transmission, and light scattering of a blue light–filtering IOL before and after power adjustment by a femtosecond laser obtained through increased hydrophilicity of targeted areas within the optic, creating the ability to build a refractive‐index‐shaping lens within an existing IOL. Setting : John A. Moran Eye Center, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Ten CT Lucia 601PY single‐piece yellow hydrophobic acrylic IOLs were used in this study. The IOL power and MTF were measured with a power and modulation transfer function device. Light transmission was measured using a Lambda 35 UV‐VIS spectrophotometer. Backlight scattering was assessed with a Scheimpflug camera within the IOL substance. All measurements were done with hydrated IOLs. The IOLs were also evaluated under light microscopy (LM) before and after laser adjustment. Results : After laser adjustment, a mean power change of −2.037 diopters was associated with a MTF change of −0.064 and a light transmittance change of −1.4%. Backlight scattering increased within the IOL optic in the zone corresponding to the laser treatment at levels that are not expected to be clinically significant. Treated areas within the optic could be well appreciated under LM without damage to the IOLs. Conclusion : Power adjustment of a commercially available hydrophobic acrylic blue light–filtering IOL by a femtosecond laser produced an accurate change in dioptric power while not significantly affecting the quality of the IOL.